Tecnologia e organização da informação VI TOI 2020: Base para a Criação de Laboratório de Ensino - Paletta, Francisco Carlos (2020)
The TOI - International Conference on Technology and Information Organization - is an initiative of the "Observatory of the Labor Market in Information and Documentation" research group (OMTID - CNPq) of the School of Communications and Arts of the University of São Paulo. The 4th TOI will take place in May 2018, in academic and scientific collaboration with the 15th CONTECSI FEA-USP, bringing together Information Science researchers, students and professionals - Librarianship, Archival Science and Museology, with the goal of promoting reflection and dialogue about relevant topics, as well as contributing to the integration of the academic and the professional environments, strengthening the interest in research, and sharing knowledge about the most innovative practices in this area. The program of this event covers the following fields of knowledge: Information and Knowledge Management; Technology and Information Systems; Digital Libraries and Repositories; Document Digitization, Knowledge Organization, Conservation and the Preservation of Information; Metadata; Digital Curation; Information Ethics; Digital Humanities; Labor Market and Entrepreneurship; Big Data; Data Science; Internet of Things; Artificial Intelligence.